Ageing and the group-reference effect in memory. Issue 6 (2nd July 2016) - Lee, Hyeon-Nyeon; Rosa, Nicole M.; Gutchess, Angela H.
Abstract : The present study examines age differences in the memory benefits from group-referncing. While prior work establishes that the memory performance of younger and older adults similarly benefits from relating information to the self, this study assessed whether those benefits extend to referencing a meaningful group membership. Young and older adult participants encoded trait words by judging whether each word describes themselves, describes their group membership (selected for each age group), or is familiar. After a retention interval, participants completed a surprise recognition memory test. The results indicate that group-referencing increased recognition memory performance compared to the familiarity judgements for both young and older groups. However, the group-reference benefit is limited, emerging as smaller than the benefit from self-referencing. These results challenge previous findings of equivalent benefits for group-referencing and self-referencing, suggesting that such effects may not prevail under all conditions, including for older adults. The findings also highlight the need to examine the mechanisms of group-referencing that can lead to variability in the group-reference effect.